An Exploratory Survey on the Adoption of Blockchain Technology in Streamlining Malaysia Real Estate During Covid-19 Pandemic (International Journal of Built Environment and Sustainability, 2022)
The global pandemic outbreak of Covid-19 and the restrictions on movement have created an unprecedented crisis for the real estate industry with mounting pressure including on property management. The higher-than-normal occupancy and load especially on strata residential buildings during the movement control order (MCO) leads to a more crucial task for property managers to ensure that every part of the building was in good working order. A high transmissible virus poses various challenges in property managers’ jobs including maintenance, inspections, viewing, and marketing the property. Accordingly, the pandemic has created a greater sense of urgency than before for real estate companies to increase technology usage by having an automated real estate record involving the buying or selling process. This study aims to explore the potential opportunities of blockchain adoption in the real estate management process. The objectives of this study are: i) to investigate the challenges of real estate managers in managing the real estate during the pandemic; ii) to study the benefits of blockchain technology adoption in the real estate management process, and (iii) to examine the opportunities of blockchain to enhance in streamlining the real estate management process. This research engages with the qualitative nature of the research strategy due to the explorative character by conducting the unstructured interview with the real estate players involved in managing the properties. All the collected materials have been transcribed and categorized to ensure that they could be analysed through NVivo, a qualitative data analysis programme. The expected outcome of this study will provide scientific evidence on the readiness of the Malaysian real estate industry to embrace technology by digitalizing the property management which is in line with the vision of the government to ensure Malaysia makes the Digital Leap into the Fourth Industrial Revolution (IR 4.0)
Keywords: Covid-19 Pandemic, Property Management Process, Blockchain Technology, Digitalization, Malaysia.